2020
DOI: 10.3310/hta24570
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-impregnated central venous catheters for preventing neonatal bloodstream infection: the PREVAIL RCT

Abstract: Background Clinical trials show that antimicrobial-impregnated central venous catheters reduce catheter-related bloodstream infection in adults and children receiving intensive care, but there is insufficient evidence for use in newborn babies. Objectives The objectives were (1) to determine clinical effectiveness by conducting a randomised controlled trial comparing antimicrobial-impregnated peripherally inserted central ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 113 publications
2
5
1
1
Order By: Relevance
“…The PREVAIL trial in neonates reported similar findings to ours with no evidence to support the use of the miconazole and rifampicin-impregnated catheters over the conventional catheter (12). The CATCH trial in children also reported no significant difference or superiority of the antimicrobialimpregnated catheters over the conventional ones (13).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The PREVAIL trial in neonates reported similar findings to ours with no evidence to support the use of the miconazole and rifampicin-impregnated catheters over the conventional catheter (12). The CATCH trial in children also reported no significant difference or superiority of the antimicrobialimpregnated catheters over the conventional ones (13).…”
Section: Discussionsupporting
confidence: 70%
“…The use of antimicrobial-impregnated central venous catheters (CVCs) has been recently recommended for patients at high risk of infection in addition to all other preventive measures (10,11). The antimicrobial-impregnated catheter PremiStar; Vygon, Swindon, UK is miconazole and rifampicin-impregnated PICC, designed and manufactured aiming to reduce the incidence of CLABSI in newborns, by the combined synergistic effect of the two medications (12). Extruded polyurethane tubes are placed into a solution made of two anti-infective substances.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial-impregnated catheters are recommended if no other measures result in a CLABSI reduction. 10,17 In line with a recent study by Gilbert et al, 29 the type of VAD (antimicrobial or conventional) did not affect the risk for CLABSI and therapy failure in this study.…”
supporting
confidence: 88%
“…Other approaches for preventing CVC-related infection, such as antimicrobial CVC, needleless IV access devices, antimicrobial dressing, etc., are in use as well [59,60]. One of the antibiotic combinations used in the impregnation of CVC is minocycline/rifampin, or for infants, miconazole and rifampin [61]. The use of different coatings, such as chlorhexidine and gluconate or silver sulfadiazine, reduced the risk for CRBSI compared to the standard non-coated catheters [62].…”
Section: Central Line-associated Bloodstream Infections Including Catheter-related Infectionsmentioning
confidence: 99%